Pengenalan Literasi Digital pada Anak Usia Dini - Apriyanto A.J. Pauweni; Amira Baehaki; Nur Fauziah Lumbin; Andi Aulia (Jambura Early Childhood Education Journal, 2021)
Introduction to Digital Literacy in Early Childhood: This article was written using the literature review method, namely an explanation of the theory, findings and research materials obtained from the material to be used as the basis for research in developing a clear frame of mind from the problem solver who wants to be researched. Digital literacy is basic knowledge that is supported by connected information technology. This writing has the aim of introducing digital literacy to early childhood. In addition, the benefits of digital literacy for early childhood are that children can gain new positive knowledge when using it properly and correctly. Children can also get to know the development of technology, information, and communication in this day and age. Therefore, to introduce digital literacy to children, there are several stages that children will go through in the process of introducing digital literacy, namely as follows: Digital literacy movement in the family, digital literacy movement in schools, and literacy movement in society.